The financial factors in sustaining financial wellbeing among potential pensioners at UiTM Kedah / Siti Norfazlina Yusoff...[et al.] - Yusoff, Siti Norfazlina; Ramli, Shahriza Ilyana; Kamarunzaman, Nur Zafifa (2014)
The demographic profile of Malaysian is experiencing the major shifts and it has led to a new phenomenon emerged so called aged society. This new phenomenon has spawned into the public sector, as response to situation Malaysian government has taken action by increasing the legal retirement age from 58 to 60 years old. However, this age cohort usually had been perceived as economically non-productive and facing health problems by many, thus this action just provide an immediate form of solution rather a long-term determination. Due to that problem , a proper pension trajectory precautionary measure is significant for public retirees and strong ties of social networks is needed for maintaining their financial dependency. The social networks is important in providing them with a 'sense of belongingness' with others, could help them feel more confidence after getting retired. Therefore, this research will identify the important of pension trajectories for public retirees and how social networks contribute to those people. The study will focus on potential pensioners at Universiti Teknologi MARA (UiTM Kedah}. The sample will be chosen using census study and a set of questionnaire will be created based on the literatures to gain facts and observed variables . The expected outcome of this research is attempted to improve the existing model for pension trajectories precautionary for public retires and intends to provide new insight on relational data which could interpret the financial well-being of individuals. The finding of this research can be further studied by future researchers and academicians in improving financial wellbeing of pensioners thus can lead to better quality of life.